Incidence of and risk factors for major haemorrhage in patients treated with ibrutinib: An integrated analysis. (2nd December 2018) - Brown, Jennifer R.; Moslehi, Javid; Ewer, Michael S.; O'Brien, Susan M.; Ghia, Paolo; Cymbalista, Florence; Shanafelt, Tait D.; Fraser, Graeme; Rule, Simon; Coutre, Steven E.; Dilhuydy, Marie‐Sarah; Cramer, Paula; et al.
Summary: Ibrutinib, a Bruton tyrosine kinase inhibitor, is approved for treatment of various B‐cell malignancies. In ibrutinib clinical studies, low‐grade haemorrhage was common, whereas major haemorrhage (MH) was infrequent. We analysed the incidence of and risk factors for MH from 15 ibrutinib clinical studies ( N = 1768), including 4 randomised controlled trials (RCTs). Rates of any‐grade bleeding were similar for single‐agent ibrutinib and ibrutinib combinations (39% and 40%). Low‐grade bleeding was more common in ibrutinib‐treated than comparator‐treated patients (35% and 15%), and early low‐grade bleeding was not associated with MH. The proportion of MH in RCTs was higher with ibrutinib than comparators (4.4% vs. 2.8%), but after adjusting for longer exposure with ibrutinib (median 13 months vs. 6 months), the incidence of MH was similar (3.2 vs. 3.1 per 1000 person‐months). MH led to treatment discontinuation in 1% of all ibrutinib‐treated patients. Use of anticoagulants and/or antiplatelets (AC/AP) during the study was common ( 50% of patients) and had an increased exposure‐adjusted relative risk for MH in both the total ibrutinib‐treated population (1.9; 95% confidence interval, 1.2–3.0) and RCT comparator‐treated patients (2.4; 95% confidence interval, 1.0–5.6), indicating that ibrutinib may not alter the effect of AC/AP on the risk of MH in B‐cell malignancies.